The Use Of Eye And Hand Coordination Analysis Approach To Shooting Accuracy In The Sport Of Petanque: A Systematic Review - Boby Helmi; Taufiq Hidayah; Harry Pramono; Mugiyo Hartono (Universitas Negeri Semarang, 2024)
The purpose of this study was to determine how hand eye coordination analysis can provide accuracy in petanque shooting techniques. This review study followed PRISMA standards for systematic reviews and meta-analyses. Studies had to be published within the previous five years, from January 2020 to July 2024. This review consists of nine studies. In four research articles, it focuses on analyzing hand eye coordination on petanque shot results. Five articles were about accuracy training to improve petanque shot accuracy. This article presents an analysis of hand-eye coordination. Analyzing hand-eye coordination helps players understand how power, speed and posture affect shots, helping players achieve more accurate shots